2017
DOI: 10.7554/elife.26876
|View full text |Cite
|
Sign up to set email alerts
|

The DREAM complex through its subunit Lin37 cooperates with Rb to initiate quiescence

Abstract: The retinoblastoma Rb protein is an important factor controlling the cell cycle. Yet, mammalian cells carrying Rb deletions are still able to arrest under growth-limiting conditions. The Rb-related proteins p107 and p130, which are components of the DREAM complex, had been suggested to be responsible for a continued ability to arrest by inhibiting E2f activity and by recruiting chromatin-modifying enzymes. Here, we show that p130 and p107 are not sufficient for DREAM-dependent repression. We identify the MuvB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(108 citation statements)
references
References 71 publications
6
102
0
Order By: Relevance
“…5C; q value < 0.0001). Using a strategy similar to that used for type B and the PRC2 complex, we took advantage of recently published dominant-negative forms of 2 MuvB core members, LIN37 (41) and LIN52 (42). It has been shown that mutations in 2 small domains in LIN37 (CD1 and CD2) result in the loss of the repressive function of the DREAM complex (LIN37-WT [amino acids 1 through 243] and LIN37-DN) (41), and inhibiting phosphorylation of serine28 on LIN52 results in similar phenotypes (LIN52-WT [1 through 116] and LIN52-DN) (42).…”
Section: Resultsmentioning
confidence: 99%
“…5C; q value < 0.0001). Using a strategy similar to that used for type B and the PRC2 complex, we took advantage of recently published dominant-negative forms of 2 MuvB core members, LIN37 (41) and LIN52 (42). It has been shown that mutations in 2 small domains in LIN37 (CD1 and CD2) result in the loss of the repressive function of the DREAM complex (LIN37-WT [amino acids 1 through 243] and LIN37-DN) (41), and inhibiting phosphorylation of serine28 on LIN52 results in similar phenotypes (LIN52-WT [1 through 116] and LIN52-DN) (42).…”
Section: Resultsmentioning
confidence: 99%
“…Using a strategy similar to that used for type B and the PRC2 complex, we took advantage of recently published dominant-negative forms of two MuvB core members, LIN37 (41) and LIN52 (42). It has been shown that mutations in two small domains in LIN37 (CD1 and CD2) result in the loss of the repressive function of the DREAM complex (LIN37-WT (1-243aa) and LIN37-DN) (41), and inhibiting phosphorylation of Serine28 on LIN52 results in similar phenotypes (LIN52-WT (1-116) and LIN52-DN) (42). We performed qRT-PCR analysis of fourteen genes that were all significantly upregulated in type C, some of which were known DREAM targets (MYBL2, FOXM1, TTK, PBK, MELK, and CDK1) (43).…”
Section: Loss Of the Dream Complex In Type Cmentioning
confidence: 99%
“…LIN52 mediates MuvB association with p130 to form DREAM (25,28). LIN9 and LIN37 have poorly characterized biochemical functions, but are required for MuvBregulated gene expression (18,29).…”
mentioning
confidence: 99%